2016
DOI: 10.1016/j.jgr.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal fertilizer application for Panax notoginseng and effect of soil water on root rot disease and saponin contents

Abstract: BackgroundBlind and excessive application of fertilizers was found during the cultivation of Panax notoginseng in fields, as well as increase in root rot disease incidence.MethodsBoth “3414” application and orthogonal test designs were performed at Shilin county, Yunnan province, China, for NPK (nitrogen, phosphorus, and potassium) and mineral fertilizers, respectively. The data were used to construct the one-, two-, and three-factor quadratic regression models. The effect of fertilizer deficiency on root yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 18 publications
4
42
0
1
Order By: Relevance
“…Similar studies have been conducted by other workers evaluating the effect of cultivation conditions, including application of fertilizer, on saponin content of a range of plant species: for example, Hosoda and Noguchi (1990) working on Bupleurum falcatum; Osuagwu and Nwosu (2006) on Ocimum gratissimum; Azzaz et al (2009) on Foeniculum vulgare; Ibrahim et al (2013) on Labisia pumila; Mary and Nithiya (2015) on Solanum nigrum, Mulyana et al (2015) on Coleus amboinicus and Xia et al (2016) on Panax notoginseng. Results of a pot experiment evaluating the effect of three different planting media and four different rates of application of a standard NPK fertilizer on the aroid species Anchomanes difformis showed that a mixed medium of soil and cocopeat (1:1) together with a fertilizer application equivalent to 100 kg/ha NPK (15% N, 15% P 2 O 5 , 15% K 2 O) was the best of the tested treatments not only for plant growth and rhizome yield but also for increasing saponin content of the rhizomes.…”
Section: Saponin Contentsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar studies have been conducted by other workers evaluating the effect of cultivation conditions, including application of fertilizer, on saponin content of a range of plant species: for example, Hosoda and Noguchi (1990) working on Bupleurum falcatum; Osuagwu and Nwosu (2006) on Ocimum gratissimum; Azzaz et al (2009) on Foeniculum vulgare; Ibrahim et al (2013) on Labisia pumila; Mary and Nithiya (2015) on Solanum nigrum, Mulyana et al (2015) on Coleus amboinicus and Xia et al (2016) on Panax notoginseng. Results of a pot experiment evaluating the effect of three different planting media and four different rates of application of a standard NPK fertilizer on the aroid species Anchomanes difformis showed that a mixed medium of soil and cocopeat (1:1) together with a fertilizer application equivalent to 100 kg/ha NPK (15% N, 15% P 2 O 5 , 15% K 2 O) was the best of the tested treatments not only for plant growth and rhizome yield but also for increasing saponin content of the rhizomes.…”
Section: Saponin Contentsupporting
confidence: 55%
“…The primary soil nutrients needed for all plant growth are nitrogen, phosphorus and potassium (NPK) (Dwidjoseputro 1983;Ariani, 2009;Pratikta et al 2013;Sukamto et al 2014;Sahoo et al 2015). External application of major nutrients is beneficial for better growth and phytochemical composition including saponin content of various plants (Hosoda and Noguchi 1990;Singh et al 2004;Osuagwu and Nwosu, 2006;Abdelaziz et al 2007;Azzaz et al 2009;Ibrahim et al 2013;Mary and Nithiya, 2015;Mulyana et al 2015;Xia et al 2016). Hence, the immediate focus of the research reported here has been to identify an effective planting medium and to optimize the dosage of a standard NPK fertilizer, to ensure good plant growth and high saponin content of Anchomanes difformis.…”
Section: Introductionmentioning
confidence: 99%
“…Over 85% total production of P.notoginseng is gained from Wenshan Prefecture of Yunnan Province, China (Szakiel et al, 2011b). However, according to a field survey, the content of organic matter, total nitrogen, and total phosphorus in the soil after P.notoginseng planting is higher than that in soils without planting, especially for nitrogen and potassium available concentration (Xia et al, 2016). Thus, nutrients in P.notoginseng planting soil is seriously imbalanced.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nutrients in P.notoginseng planting soil is seriously imbalanced. Unfortunately, only a few researches have been carried on how to reduce fertilizer input in P.notoginseng cultivation, but the results are not so persuasive (Xia et al, 2016). Most studies on P.notoginseng mainly focus on phytochemistry (Wang et al, 2016), pharmacy (Uzayisenga et al, 2014) and quality assessment (Toh et al, 2010;Li et al, 2013;Yao et al, 2011;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(Kim et al, 2010;Lee et al, 2003;Nam et al, 2002;Park et al, 1982) (Table 4), Rh2만이 질산태 질소 및 유효태 인산 과 유의적 상관관계가 있었다 (Table 5). 화학비료는 인삼 생육과 진세노사이드를 모두 증진시키거나, 생육만 증진시 킨다는 보고가 있다 (Park et al, 1986;Xia et al, 2016).…”
unclassified